New private law theory : a pluralist approach - Grundmann, Stefan, 1958-; Micklitz, Hans-W.; Renner, Moritz, 1981- (Cambridge : Cambridge University Press, 2021)
New Private Law Theory opens a new pathway to private law theory through a pluralistic approach. Such a theory needs a broad and stable foundation, which the authors have built here through a canon of nearly seventy texts of reference. This book brings these different texts from different disciplines into conversation with each other, grouping them around central questions of private law and at the same time integrating them with the legal doctrinal analysis of example cases. This book will be accessible to both experienced and early career scholars working on private law.
The inside and the outside of law? (Grundmann) -- Private law and sociology (Renner) -- Economics and private law institutions (Grundmann) -- Private law and theories of communication (Renner) -- Comparative law and legal history (Micklitz) -- Societal order and private law (Grundmann) -- Values in private law (Renner) -- Constitutionalisation, regulation, and private law (Micklitz) -- Democracy and private law (Micklitz) -- Formalism, substantive, and procedural justice -- Negotiation, the function of contract and the 'justice of consensus' (Grundmann) -- Knowledge and information (Grundmann) -- Private power (Renner) -- Non-discrimination (Renner) -- Risk, tort, and liability (Micklitz) -- Digital architecture of private law relations (Micklitz) -- Between market and hierarchy (Grundmann) -- Person, civil status, and private law (Micklitz) -- Theory of the corporation (Renner) -- Actors in organizations (Grundmann) -- The principal's decision : exit, voice, and loyalty (Grundmann) -- Organizations and public goods (Micklitz) -- Law as a product (Micklitz) -- Multi-level governance and economic constitution (Micklitz) -- Transnational Law (Renner) -- Private ordering (Renner) -- The shadow of the law and social embeddedness (Grundmann).
Title from publisher's bibliographic system (viewed on 09 Apr 2021).
Keywords: Civil law; Civil law -- Social aspects